2011
DOI: 10.1177/039463201102400314
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Neutrophil Granulocytes from Patients with Head and Neck Squamous Cell Carcinoma Functionally Differ from Their Counterparts in Healthy Donors

Abstract: Solid tumors such as head and neck squamous cell carcinoma (UNSee) display an intense interaction between tumoral factors and the immune system. Functional modulation of tumor-infiltrating and peripheral blood immune cells plays an important role during tumor progression. In this pilot study we compared biological functions of polymorphonuclear granulocytes (PMN) from the peripheral blood of UNSee patients and healthy subjects. PMN were simultaneously isolated from the peripheral blood of UNSee patients and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 35 publications
4
84
0
1
Order By: Relevance
“…The neutrophils from HNSCC showed lower inducible production of ROS, reduced spontaneous apoptosis and increased number of immature neutrophils [374]. The serum concentration of neutrophil related cytokines was higher in HNSCC patients [374].…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 96%
See 2 more Smart Citations
“…The neutrophils from HNSCC showed lower inducible production of ROS, reduced spontaneous apoptosis and increased number of immature neutrophils [374]. The serum concentration of neutrophil related cytokines was higher in HNSCC patients [374].…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 96%
“…Studies on neutrophils from patients with head and neck squamous cell carcinoma (HNSCC) showed that these neutrophils differ from their counterparts in healthy donors [374]. The neutrophils from HNSCC showed lower inducible production of ROS, reduced spontaneous apoptosis and increased number of immature neutrophils [374].…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of TINs has been shown to be a strong, independent prognostic factor for recurrence-free and overall survival in metastatic 2 and localized clear cell renal cell carcinoma 3 , and in head and neck squamous cell carcinoma 4 , and a high neutrophil count has been found to be associated with a favorable prognosis in gastric cancer 5 . In contrast, the number of TINs was found to correlate with a high tumor grade in human gliomas 6 and to be related to more aggressive types of pancreatic tumors 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also demonstrate a convincing role for IL-18 in atopic responses, including atopic inflammatory diseases (46)(47)(48)(49)(50). Moreover, IL-18 directly stimulates basophils and mast cells to produce Th2 cytokines and histamine independently of IgE.…”
mentioning
confidence: 96%